MANAJEMEN DAN PENGUKURAN KINERJA PEMERINTAHAN - PRIYATNO HARSASTO, PRIYATNO HARSASTO (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
AbstractManagement of Government Performance consists of a set of processes that helpgovernment organizations optimize their performance. It provides a framework for organizing,automating, and analyzing business methodologies, metrics, processes and systems that drive theirperformance. In the past, government have sought to drive strategy down and across theirorganizations; they have struggled to transform strategies into actionable metrics and they havegrappled with meaningful analysis to expose the cause-and-effect relationships that, if understood,could give profitable insight to their operational decision-makers. Recent development has facilitatedgovernments to choose indicators to measure government performance more accurate and easily.Key words: Government performance, performance indicators, benchmarking